Midurethral Sling Removal or Revision in Women with Chronic Pain. Issue 5 (13th May 2022) - Rockefeller, Nicholas F.; Petersen, Timothy R.; Jeppson, Peter C.; Dunivan, Gena; Ninivaggio, Cara; Meriwether, Kate; Gallegos, Maxx A.; Komesu, Yuko M.
Abstract : Objectives: The objectives of this study are (1) to estimate the incidence of midurethral sling revision/removal in women with preexisting pain diagnoses versus those without these diagnoses and (2) to describe associations between numbers and type of pain diagnoses with revision/removal. Methods: Women who underwent midurethral sling surgery between 2009 through 2014 were identified in the MarketScan database and tracked and December 31, 2014. Patients with preoperative chronic pain diagnoses (fibromyalgia, endometriosis, irritable bowel, dyspareunia, low back pain, temporomandibular joint syndrome, interstitial cystitis, pelvic/perineal pain) were compared with controls (those without these diagnoses) regarding mesh sling revision/removal. Logistic regression identified variables associated with mesh revision/removal, and survival analysis compared timing of mesh removal/revision. Results: There were 161, 459 women who underwent midurethral sling surgery (pain, 83, 484; nonpain, 77, 975). Pain and nonpain groups differed in age (52.1 vs 53.5 years, P < 0.01) and insurance status ( P < 0.01), with the pain group more commonly living in the South or West. Mean follow-up was 42.3 months. Cumulative risk for sling revision/removal was higher in patients with 1 pain diagnosis relative to controls (relative risk, 1.54; 95% confidence interval [CI], 1.41–1.54). Risks increased with increased pain diagnoses (≥4 diagnoses; relative risk, 3.13; 95% CI, 2.81–3.47). Pelvic pain conditions had greatest odds of mesh revision/removal (dyspareunia adjusted odds ratio [aOR], 2.44; 95% CI, 2.23–2.63; interstitial cystitis aOR, 1.46; 95% CI, 1.27–1.66; pelvic/perineal pain aOR, 1.41; 95% CI, 1.33–1.48). Co-occurrence of dyspareunia and interstitial cystitis or pelvic/perineal pain had 12.7% cumulative incidence of sling revision/removal. Cox proportional hazards revealed greatest risk for those with pelvic pain conditions (hazard ratio, 2.40; 95% CI, 2.13–2.70). Conclusions: Chronic pain diagnoses increased risk of midurethral sling revision/removal; pelvic pain and numbers of diagnoses increased this risk.